2002
DOI: 10.1080/13550280290100480
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of viral RNA in the brain of offspring to mice infected with influenza A/WSN/33 virus during pregnancy

Abstract: Epidemiological studies have indicated an association between influenza A virus infections during fetal life and neuropsychiatric diseases. To study the potential for influenza A virus infections to cause nervous system dysfunctions, we describe a mouse model using intranasal instillation of the mouse neuroadapted influenza A/WSN/33 strain in pregnant mice. Viral RNA and nucleoprotein were detected in fetal brains and the viral RNA persisted for at least 90 days of postnatal life. We have, thus, obtained evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…Two of these proteins, AQP4 and CX43, are likewise altered in autistic brain (Fatemi et al unpublished observations) and a third may be implicated in the macrocephaly, which is commonly observed in autistic subjects (Fombonne et al 1999;Lainhart et al 2006) as well as in our animal model (Fatemi et al 2002a). Most importantly, the weight of accumulated evidence so far showing presence of gliosis (Fatemi et al 2002b), pyramidal cell atrophy (Fatemi et al 2002a), and upregulation of nucleolin, as well as previous supportive evidence (Aronsson et al 2001;Aronsson et al 2002), showing persistence of influenza viral RNA in brain implicate a potential viral effect on the developing fetal brain.…”
Section: Discussionmentioning
confidence: 77%
“…Two of these proteins, AQP4 and CX43, are likewise altered in autistic brain (Fatemi et al unpublished observations) and a third may be implicated in the macrocephaly, which is commonly observed in autistic subjects (Fombonne et al 1999;Lainhart et al 2006) as well as in our animal model (Fatemi et al 2002a). Most importantly, the weight of accumulated evidence so far showing presence of gliosis (Fatemi et al 2002b), pyramidal cell atrophy (Fatemi et al 2002a), and upregulation of nucleolin, as well as previous supportive evidence (Aronsson et al 2001;Aronsson et al 2002), showing persistence of influenza viral RNA in brain implicate a potential viral effect on the developing fetal brain.…”
Section: Discussionmentioning
confidence: 77%
“…However, having performed a careful review of the pertinent literature, we found that, in the majority of studies in which neural spread of the A/WSN/33 virus has been shown to occur, this was a result of i.p. infection of pregnant dams (49,50), intranasal infection of immunodeficient mice (23,51), direct intracerebral inoculation (52,53), or infection of suckling mice (54)(55)(56). Indeed, we were able to identify only two studies that described spread to the brain following intranasal administration of influenza A/WSN/33 virus to adult immunocompetent mice, and in both cases, mice were infected using an inoculum 100 or 500 times greater than that used in our studies (57,58).…”
Section: Fig 7 Lung Compliance and Airway Resistance Were Not Alteredmentioning
confidence: 71%
“…The lack of evidence for direct infection of the fetus (Shi et al, 2005) (but see Aronsson et al, 2002), and the fact that multiple pathogens cause similar results in humans [e.g., influenza (Brown, 2006), herpes (Babulas et al, 2006), rubella (Chess, 1977)], indicates that MIA, in general, is detrimental to the developing brain. The data presented here confirms previous reports (see Introduction) that MIA causes behavioral and geneexpression changes in the offspring of pregnant mice.…”
Section: Discussionmentioning
confidence: 99%